Dissipative preparation of phase- and number-squeezed states with ultracold atoms - Caballar, Roland Cristopher F.; Diehl, Sebastian; Mäkelä, Harri; Oberthaler, Markus K.; Watanabe, Gentaro (Physical review. A, Atomic, molecular, and optical physics, 2014)
We develop a dissipative quantum state preparation scheme for the creation of phase- and number-squeezed states. It utilizes ultracold atoms in a double-well configuration immersed in a background Bose-Einstein condensate, with the latter consisting of an atom species different from the atoms in the double well and acting as a dissipative quantum reservoir. We derive a master equation for this system starting from microscopic physics and show that squeezing develops on a time scale proportional to 1/N, where N is the number of particles in the double well. This scaling, caused by bosonic enhancement, allows us to make the time scale for the creation of squeezed states very short. The lifetime of squeezed states is limited by dephasing arising from the intrinsic structure of the setup. However, the dephasing can be avoided by stroboscopically switching the driving off and on. We show that this approach leads to robust stationary squeezed states. Finally, we provide the necessary ingredients for a potential experimental implementation by specifying a parameter regime for rubidium atoms that leads to squeezed states.
Gesehen am 16.10.2020